Yusuf Qaradawy’s Ideas on Civilization and the Development of Modern Society: Perspectives on Philosophy - Istiqomah, Imroatul (Proceeding International Conference on Religion, Science and Education, 2024)
This article outlines the ideas of the leading contemporary Islamic thinker, Shaikh Yusuf Qaradawi (1926-2022) regarding Islamic civilization and the development of modern society. A study using a philosophical perspective that explains the significance of Islamic civilization, its components, the forces that support its development, and the phases of society-building. This article first defines Islamic civilization and societal evolution before contrasting it with other Muslim philosophers who put a heavy emphasis on civilization theory, like Ibn Kholdun, Malik bin Nabi, and others. The conclusion demonstrates that Shaikh Yusuf Qaradawy stressed that the most crucial factor in launching the evolution of civilisation is developing people as civilization's actors. People need to be aware of who they are, what they stand for, and what they need to do in this life in relation to God, other people, and the environment around them. To establish an enlightened society, there must also be awareness, coordinated action, and stakeholder support. According to Al-Qaradawi, individuals who are good will build a good family and families who are good will form a decent society.